THE EFFECTIVENESS OF KUNINGAN GOVERNMENT POLICY IN WATER CONSERVATION - Suwari Akhmaddhian (Jurnal Dinamika Hukum, 2017)
Preserving environmental functions particularly water resources conservation is a shared task between government and public to achieve environmental sustainability. The purpose of this paper is to examine the effectiveness of Kuningan government policy in conserving water resources. This study uses empirical juridical method with descriptive analysis. The data collection of primary data is done by observation, interviews with related institutions while secondary data are in the form of legislation and legal theories. This research takes place in Kuningan regency, West Java province. The data are analyzed to examine the effectiveness of Kuningan Government policies in water resource conservation. The results reveal that District Regulation Number 12 Year 2007 on Water Resources Conservation and Kuningan District Regulation Number 12 Year 2011 on the Implementation of Kuningan Botanical Gardens along with other related Regulations and Government policies in Kuningan Regency have been effectively implemented. It can be seen from the sufficiently given regulations as well as community participation.Keywords: effectiveness, policy, water conservation